2017
DOI: 10.24086/cuesj.si.2017.n2a26
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Silver and Titanium Dioxide Nanoparticles on Klebsiella Pneumoniae Isolates Multi Resistant to Antibiotics and Observed by Scanning Electron Microscopy

Abstract: One hundred fifty six samples collected included: urinary tract infections, wounds, pus, burns and tonsils from patients coming to Rizgary Teaching Hospital and Rozhawa Hospital in Erbil city from March to September 2013, scrubbed and confirmed the diagnosis (33) strain which belongs to Klebsiella pneumoniae and by (21.2%) based on cultural characteristics, microscopically features and biochemical tests in addition to the API -20E.These strains sensitivity to 12 types of antibiotics. It gave the species a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Titanium dioxide powder combined with antibiotics showed a significant decrease in the MICs of the tested strains by 2-fold or greater, which suggested its activity as an efflux inhibitor according to the method reported by Lamers et al [33]. In addition, many studies have shown that combining TDN and antibiotics potentiates the antimicrobial action of different classes of antibiotics [34,35]. The combination of TDN with antibiotics increases the concentration of antibiotics at the bacterium-antibiotic interaction site, and the binding of bacteria to antibiotics [36].…”
Section: Discussionmentioning
confidence: 88%
“…Titanium dioxide powder combined with antibiotics showed a significant decrease in the MICs of the tested strains by 2-fold or greater, which suggested its activity as an efflux inhibitor according to the method reported by Lamers et al [33]. In addition, many studies have shown that combining TDN and antibiotics potentiates the antimicrobial action of different classes of antibiotics [34,35]. The combination of TDN with antibiotics increases the concentration of antibiotics at the bacterium-antibiotic interaction site, and the binding of bacteria to antibiotics [36].…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, nanoparticles release ions that can react with the -SH group of proteins that control the transporting of material, reducing their permeability. 7,9,44 Many studies detected antifungal and antibacterial activities of TDN as Duymaz et al 45 and Alhadrami et al 46 Thomas (2016) showed that antimicrobial activity of toothpastes and mouthwashes against dental plaque-causing organisms were enhanced by adding TDN. 47 Recently many studies reported that the wound dressing with TDN enhanced wound healing due to its antimicrobial and cell growth stimulation features.…”
Section: Susceptibility Of P Aeruginosa Isolates To Tdnmentioning
confidence: 99%
“…55 Many studies have shown that combining TDN potentiate the antimicrobial action of different classes of antibiotics. 2,[7][8][9] FICI is an indicator of the degree of interaction between TDN with commercial antibiotics for the 25 MDR P. aeruginosa strains. The FICI of the combination of TDN plus cefepime shows synergistic effect to all isolates (100%), ceftriaxone; showing synergistic effect against 24 strains (96%) and additive effect against one strain (4%); ciprofloxacin showing synergistic effect against 20 strains (80%) and additive effect against three (12%) and two strains were not evaluated using the combination of TDN and ciprofloxacin as both were sensitive to ciprofloxacin; amikacin, showing synergistic effect against 22 strains (88%) and additive effect against three (12%) isolates as shown in Table 3.…”
Section: Susceptibility Of P Aeruginosa Isolates To Tdnmentioning
confidence: 99%
See 1 more Smart Citation
“…They are characterized by many features, including heat resistance and less toxicity, and reveal strong activity against resistant strains of many microorganisms [ 15 , 16 ]. Also, they can be utilized as mineral element supplements which are essential for nourishing cells [ 17 ]. Nano-based titanium oxide elicited potent inhibitory activity against the growth of bacteria because of its little nano-sized and strong oxidizing activity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%